Mid-infrared fiber laser : high-power ultrafast pulse delivery and compression - Lee, Elizabeth Mei Yin (Nanyang Technological University, 2020)
Mid-infrared ultrafast pulses are useful to drive nonlinear effects towards supercontinuum generation. These mid-infrared supercontinuum light sources are useful in label-free spectral imaging on biological tissues for disease identification. Other potential applications include spectroscopy and spectral imaging for food safety and quality inspection. A high photon flux is also desirable especially in single-shot applications enabling high signal-to-noise ratios or when probing moving targets such as living cells. Fiber lasers are particularly attractive as laser sources as they offer compactness and excellent beam quality. Furthermore, their efficient heat dissipation along long fiber lengths allows high pulse repetition rates and consequently high output powers. However, there are challenges to scale the output powers in fiber lasers due to the deleterious effects of nonlinearities and modulation instability. High-power ultrafast mid-infrared lasers are also useful for material processing of semiconductors and clear polymers, and for interactions with water-rich biological tissues and biomaterials. These applications will benefit from the flexible delivery of the ultrafast pulses with low losses whilst maintaining good beam quality. However, there are challenges in delivering ultrafast mid-infrared pulses, due to silica absorption, peak power damage thresholds in glass and dispersion which distorts the pulse temporal profile. These applications will also benefit from a shorter pulse width which eliminates thermal-related effects. In this thesis, some strategies useful for power scaling in thulium-based fiber lasers namely spectral gain shaping, resonant pumping and chirped pulse amplification will be discussed. The spectral bandwidth and shape of the propagating laser light may suppress nonlinear effects. Thus, a design method to shape the spectral gain of thulium-based sources based on cascaded segments of fibers, variable pumping schemes and other parameter optimization was proposed. Experimentally, a 3-dB bandwidth of 178 nm centered at 1944.75 nm through the cascaded two-segment TDF system was achieved. The use of resonant pumping at 1940 nm in a pulsed thulium fiber amplifier system was investigated. An output power of 40 W was attained with 53 W launched pump power from the 1940 nm CW fiber laser, corresponding to an efficiency of 87%. The gain fiber 5 did not require active cooling due to the low quantum defect, thus resonant pumping method eases the cooling requirements and may potentially reduce the onset of transverse modulation instability (TMI). A compact megawatt picosecond thulium-based fiber laser system based on the chirped pulse amplification (CPA) technique was constructed. The CPA technique allowed amplification at high pulse energies, and we achieved an output pulse energy of 46.3 μJ after compression from a multipass CVBG-based compressor at 2 μm wavelengths. The megawatt picosecond pulses were then used for processing of hydrogel, a temperature-sensitive biomaterial commonly used in cell culture studies. Microchannels, pores and surface foaming were created by direct writing without the need for additives or additional processing. A relatively new hollow-core fiber, the antiresonant hollow-core fiber (AR-HCF), was studied through finite element method analysis and experimental work as a potential candidate for the delivery and compression of high-power ultrafast mid-infrared pulses. The use of a cone type AR-HCF for flexible single-mode delivery of up to 39.1 W average power of 2 μm nanosecond pulses was demonstrated, with transmission efficiencies of up to 77%. The bending performance of the AR-HCF was evaluated and the fiber maintains a Gaussian-like beam profile up to 15 cm bending diameter. The transmission of picosecond and femtosecond 2 μm pulses using the AR-HCF was studied and verified its usefulness for ultrashort pulse delivery. Finally, the use of a gas-filled AR-HCF for nonlinear pulse compression was studied through numerical modelling and experimental demonstration. The pulse propagation in a gas-filled AR-HCF was modelled based on the numerical implementation of the nonlinear Schrödinger equation. Then, the gas cell to contain each fiber end was designed and fabricated, allowing separate pressure control at both fiber ends. The shortest pulse duration obtained was 55.4 fs using a 48 cm-long AR-HCF.